The use of chronic dialysis in a resource-poor environment: demographic features and transplant readiness at Helen Joseph Hospital renal unit - Parbhoo, Dinen (My University, 2019)
Background Chronic kidney disease (CKD) places a considerable economic strain on health care systems. In South Africa resource limitations in the public sector mandate that patients with end stage renal disease (ESRD) are only offered dialysis if they qualify for renal transplant. Thus, chronic dialysis serves as a bridge to transplantation. Objectives The primary objective of this study was to describe the patients on the chronic dialysis program with regards to demographic features, aetiology of renal failure, associated chronic comorbidities and transplant readiness. Secondary objectives included the determination of the type and duration of dialysis used and the documentation of any possible differences between the haemodialysis (HD) and peritoneal dialysis (PD) groups and the HIV positive and negative patients. Methods A cross-sectional record review was conducted of all patients receiving chronic dialysis at the Helen Joseph Hospital’s Renal Unit as at September 2016. Information regarding demographic features, disease profile, year of initiation of dialysis, year of presentation, Human Immunodeficiency Virus (HIV) status and transplant readiness was collected. All data was analysed at a 95% confidence interval and a p value of <0.05 was considered significant. Results There were 92 patients on chronic dialysis, 46 each on PD and HD. The mean (SD) age of patients in this study was 43.8 years (10.8). There was a slight female predominance (51.1%). The predominant ethnic group was African (64.1%). The leading causes of ESRD were hypertension (35.9%) followed by diabetes mellitus (10.9%). The most frequent comorbidity was hypertension (98.9%) followed by HIV infection (36.1%). The median time that patients spent on dialysis before presentation for transplant listing was 2 years (range 0-9 years). At the time of analysis, 27 patients (29.4%) were eligible for transplant and 38 patients (41.3%) were in the process of transplant eligibility evaluation. Twenty-seven patients (29.4%) were ineligible for transplant. Of those eligible for transplant, 21 were listed for transplant and 6 were awaiting presentation for listing. There were no differences between the HD and PD groups or the HIV positive and negative groups with regards to qualification for transplant. Conclusion The demographic features and underlying aetiologies of our cohort are similar to national figures with only the racial composition being different. The proportion of patients listed for transplantation (22.8%) and median time for work-up (2 years) are both sub-optimal. Improved efficiency in the evaluation of transplant eligibility is required in order to optimize the appropriate allocation of dialysis in a resource-limited setting.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Masters in Medicine (MMed) Johannesburg 2019